TFPa/HADHA is required for fatty acid beta-oxidation and cardiolipin re-modeling in human cardiomyocytes - Jason W. Miklas (Nature Portfolio, 2019)
Mutations in the gene HADHA result in mitochondrial tri-functional protein (MTP) deficiency and can result in sudden infant death syndrome for which there is no treatment. Here the authors show that the MTP deficient pathology in human cardiomyocytes leads to an abnormal cardiolipin pattern and suggests that cardiolipin affecting compounds may serve as a potential therapy.